Mountain Biodiversity patterns in Southern Europe and North Africa - Gavilán, Rosario G.; Jiménez-Alfaro, Borja; Baccheta, Gianluigi; Dimopoulos, Panayotis; Mucina, Ladislav (Lazaroa, 2013)
About 19% of European population lives in the mountainous regions – a notably more than the global average. The 50% of the Earth’s population depends on the mountain resources, mainly on drinking and industrial water and energy. However, the role of the mountain regions as place of recreation and leisure should not be underestimated as it is a major source economic force in some countries but also one of sources of problems creating pressure on mountain biota and landscapes. Lazaroa, Journal of Botany, through this feature presents a collection of papers focused on biodiversity of South Europe and Northern Africa mountain ranges. Geographically, it covers the main mountain chains of Europe and of North Africa, including those of the Balkans, Dinarides, Apennines, Pyrennees, Cantabrian Mts, Sierra Nevada and a whole array of other Mediterranean mountain ranges such as the Sistema Central in the Iberian Peninsula and those of Portugal and Sicily, and finally the Atlas of North Africa.